SEPARATION OF ZIRCONIUM AND HAFNIUM WITH SIR METHOD’S (ADSORPTION AND DESORPTION ION EXCHANGE) - Dwi Biyantoro; Noor Anis Kundari; Nofriady Aziz (BATAN, 2017)
Precence of hafnium is more than 100 mg/kg making it impossible to use as cladding material in nuclear reactor, because of its high adsorption cross section thus inhibite the nuclear fission. The objective of this research is to separate Zr – Hf using SIR method that is by impregrnating extracts to resin. Extractants used are TBP and D2EHPA, resin used is XAD – 7, and feed used is Zirconium Basic Sulphate (ZBS). In this research is done variation compotition SIR, optimation process adsorption and desoprtion SIR and determintionof equation model in adsorption SIR. The result of this research is composition SIR the most effective for separation Zr – Hf is 5 : 5 for dry method’s and 7 : 3 for wet metode’s, model of equation for Zr nearly Langmuir model, model of equation for Hf nearly Freundlich model and adsorption result effenctively is comparation feed : SIR yaitu 10 mL : 1,5 g (1 : 1,5) with separation factor 30.12 ; separation efficiency Zr 31.47 % and separation efficiency Hf 42.06%.